Features and prognostic impact of distant metastases in 45 dogs with de novo stage IV cutaneous mast cell tumours: A prospective study. (23rd February 2017) - Pizzoni, S.; Sabattini, S.; Stefanello, D.; Dentini, A.; Ferrari, R.; Dacasto, M.; Giantin, M.; Laganga, P.; Amati, M.; Tortorella, G.; Marconato, L.
Abstract : Background: Distant metastases in dogs with cutaneous mast cell tumors (cMCT) are rare and incurable. The aims of this prospective study were to clarify the clinico‐pathological features of stage IV cMCTs and to identify possible prognostic factors for progression‐free interval (PFI) and survival time (ST). Material and methods: Dogs were eligible for recruitment if they had a previously untreated, histologically confirmed cMCT and if they underwent complete staging demonstrating stage IV disease. Dogs were uniformly followed‐up, whereas treatment was not standardized and included no therapy, surgery, radiation therapy, chemotherapy, tyrosine‐kinase inhibitors or a combination of these. Results: 45 dogs with stage IV cMCT were enrolled. All dogs had distant metastatic disease, and 41 (91.1%) dogs had also metastasis in the regional lymph node. Histopathological grade and mutational status greatly varied among dogs. Median ST was 110 days. Notably, PFI and ST were independent of well‐known prognostic factors, including anatomic site, histological grade, and mutational status. Conversely, tumor diameter >3 cm, more than 2 metastatic sites, bone marrow infiltration, and lack of tumor control at the primary site were confirmed to be negative prognostic factors by multivariate analysis. Conclusion: Currently, there is no satisfactory treatment for stage IV cMCT. Asymptomatic dogs with tumor diameter <3 cm and a low tumor burden, without bone marrow infiltration may be candidates for multimodal treatment. Stage IV dogs without lymph node metastasis may enjoy a surprisingly prolonged survival. The achievement of local tumor control seems to predict a better outcome in dogs with stage IV cMCT.